Advanced liposome based PEGylated microgel as a novel release system for 5-fluorouracil against MCF-7 cancer cell. (5th March 2021) - Ulker, Damla; Barut, Inci; Şener, Erol; Bütün, Vural
Graphical abstract: Highlights: Liposome-based microgels as novel drug release system for 5-FU cancer drug molecule. Sustained drug release of 5-FU loaded microgels being noncytotoxic on L929 cell line. 5-FU loaded lower toxic liposome-microgel has a good promising effect on MCF-7 cells. These systems may provide new opportunities in in-vivo drug release approaches. Abstract: Micro/nano-sized particles provide a control on optimization of the therapeutic index of cancer drugs. This study reports successful modification of the multi-responsive microgels based on a water-soluble 2-( N -morpholino)ethyl methacrylate (MEMA) monomer for sustained drug delivery of 5-fluorouracil (5-FU). PMEMA microgel hosting 5-FU loaded 1, 2-dipalmitoyl- sn -glycero-3-phosphocholine (DPPC) liposome system was successfully prepared. DPPC liposome-based PMEMA microgel system was also studied in in-vitro studies as a drug carrier and controlled drug release system in phosphate buffer solution and normal saline solution. The release of 5-FU from both PMEMA microgel and liposome-based PMEMA microgel systems was analyzed using HPLC with ultraviolet spectrophotometer detector (λ 266 nm). The cytotoxic assays of liposome-based microgel and 5-FU loaded liposome-based microgel systems were investigated using L929 and MCF-7 which are mouse fibroblast cell line and breast cancer cell line, respectively. In conclusion, PEGylated PMEMA microgel and liposome-based PEGylated PMEMA microgel system provided long-time sustained drug release of 5-FU. It has been observed that the 5-FU release from PEGylated PMEMA system was faster than that of DPPC liposome-based microgel system. Additionally, 5-FU release from DPPC liposome-based microgel system was determined to be very effective on MCF-7 breast cancer cell line, which indicates great potential for further in-vivo studies.